Four Decades Research on Higher Vocational Education: A Bibliometric Review - Khairul Hafezad Abdullah (Journal of Vocational Education Studies, 2021)
Vocational education is seen as an integral part of the educational system, either at the school level or at a post-secondary level. It is indicated that vocational education has immensely influenced life and plays a vital role in evolving societies worldwide. Thus, analysing these scientific domains evolution and creation are essential. This study discusses the bibliometric review of scholarly research performed in higher vocational education in recent years. The study uses the Scopus database and a wide variety of bibliometric metrics, including publications, citations, and publishing patterns. A graphical visualisation of bibliographic details using the VOS viewer software is also presented. Results show that the number of studies covering this subject has fluctuated, with the highest number of publications being 65 in 2020. Often, by reviewing publications and research areas, it can be construed that higher vocational education research is diverse, including social sciences, computer science, and engineering. The bibliometric review conducted offers a rigorous and thorough view of higher vocational education research that may benefit higher vocational education practitioners and researchers keen on the pursuit of enhancing or discovering new knowledge in this field.